Implementasi Pengembangan Sistem Manajemen Pengetahuan Organisasi di PT Indonesia Partner Solution - Suryatama Mahardika (Journal of Current Research in Management, Policy, and Social Studies, 2025)
PT. Indonesia Partner Solution is a company providing outsourcing services established in Sidoarjo, East Java since 2010 and operates to provide contract labor needs such as cleaning services, security personnel, administrative staff, customer service, production operators, sales personnel and other labor position needs with outsourcing status. Armed with the experience owned by PT. Indonesia Partner Solution has twenty branch offices spread throughout Indonesia, with a total of 52 (fifty-two) core employees. In this study, the author will explain the implementation of the organizational knowledge management system at PT. Indonesia Partner Solution where this company is a service company whose operational activities are related to human resources. Furthermore, the author will explain what is meant by human resources are company employees. So that in a company an employee is expected to be able to carry out management functions well, accompanied by optimal knowledge management. An employee must be able to carry out planning, development, maintenance, use and assessment of human resources to facilitate the effective use of their performance in order to achieve personal goals and organizational goals, especially to improve their performance. In this study, an assessment of sixty-four percent of respondents stated that they strongly agree, thirty-one percent stated that they agree, four percent stated that they agree and one percent stated that they disagree that the implementation of the knowledge management system at PT. Indonesia Partner Solution is running well. Where in the assessment, sixty-four percent of respondents felt that they had obtained benefits from the knowledge management system implemented by the company. This means that the company has shown that it has the characteristics to become a learning organization.